Holocen strandforskyvning ved Skånland, Troms / Holocene shore displacement at Skånland, Troms, northern Norway - Lid, Kjersti Aalvik (The University of Bergen, 2020)
The aim for this master thesis was to construct a relative sea-level curve for the area of Skånland municipality, northern Norway. The relative sea-level curve is based on the results from bio- and litostratigraphic investigations of two basins, Store Trøsevatnet (73,5 m a.s.l.) and Svartvatnet (38,9 m a.s.l.), combined with results from previous work in the area. A simple type of phytoplankton analysis has been preformed on sediment cores from both basins, which is based on the fact that the composition of microscopic phytoplankton (green algae and dinoflagellate cysts) in the sediment reflects changes in the depositional environment (marine or fresh water). By using this method it was determined that Store Trøsevatnet did not qualify as an isolation basin, which indicates that the marine limit for the area must be located below 73,5 m a.s.l. For Svartvatnet, the results from the phytoplankton analysis were combined with the results from loss on ignition and X-ray fluorescence (XRF) scanning to determine the isolation contact. In total, six samples for radiocarbon dating were collected from Svartvatnet, and the isolation contact was dated to 9315 ± 100 calender years before present (cal. yr BP). One radiocarbon date was also preformed on basal sediments from Store Trøsevatnet, which gave an age of 10695 ± 205 cal. yr BP, and this represents the minimum age for when the area became deglaciated. To avoid problems related to the hard-water effect, terrestrial plant macrofossils were preferred for dating. However, two of the samples from Svartvatnet were preformed on marine material, which included a single shell of Macoma calcarea and unidentified shell fragments, respectively. Based on the results from the phytoplankton analysis, radiocarbon dating, and XRF-data, the brackish transitional phase in Svartvatnet seems to have been relatively short (2 cm), and represent a time period of about 180 years. This indicates that the rate of sea level regression was relatively fast (1,5 cm/yr) at the time of isolation. The ...